2022
DOI: 10.3390/cells11132026
|View full text |Cite
|
Sign up to set email alerts
|

Mechanotransduction in Skin Inflammation

Abstract: In the process of mechanotransduction, the cells in the body perceive and interpret mechanical stimuli to maintain tissue homeostasis and respond to the environmental changes. Increasing evidence points towards dysregulated mechanotransduction as a pathologically relevant factor in human diseases, including inflammatory conditions. Skin is the organ that constantly undergoes considerable mechanical stresses, and the ability of mechanical factors to provoke inflammatory processes in the skin has long been known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 264 publications
0
14
0
Order By: Relevance
“…In our study, elastin levels were also found to increase gradually with increasing PLLA concentration. Previous studies have confirmed that elastin, a type of dermal ECM cross‐linked fiber, together with collagen, forms the thicker connective tissue of the dermis, proving the mechanical framework and elasticity needed for the skin 24,25 . Therefore, cosmetic skin materials should mainly be biomaterials based on collagen and elastin.…”
Section: Discussionmentioning
confidence: 98%
“…In our study, elastin levels were also found to increase gradually with increasing PLLA concentration. Previous studies have confirmed that elastin, a type of dermal ECM cross‐linked fiber, together with collagen, forms the thicker connective tissue of the dermis, proving the mechanical framework and elasticity needed for the skin 24,25 . Therefore, cosmetic skin materials should mainly be biomaterials based on collagen and elastin.…”
Section: Discussionmentioning
confidence: 98%
“…They modify mechanosensitive pathways which, in turn, impacts skin homeostasis. At the same time, in some patients intrinsic factors including autoimmune responses, mutations, and others, can be responsible for inflammatory skin disorders [ 13 ]. For instance, the two most diffuse inflammatory skin conditions mediated by autoimmune response are psoriasis and atopic dermatitis, both involving T-cells [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 , 3 , 4 , 5 , 6 In contrast, the compromised epidermal barrier in inflamed skin, such as in psoriasis and atopic dermatitis, is explained mainly by the improper keratinocyte differentiation, sphingolipid synthesis, and, as a result, the malformation of the cornified layer in the multi-layered epidermis. 7 , 8 , 9 , 10 , 11 , 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…To the present date, the regulation and interconnection of cell-cell adhesion, cell contractility, and the downstream mechanosignaling in inflamed epidermis remain unclear. 13 At the same time, innovative topical therapies for chronic inflammatory skin conditions such as psoriasis are much needed. 74 In this study, we have modeled psoriatic inflammation using a specific cytokine stimulation 75 of non-differentiated human keratinocytes and reconstructed human epidermis (RHE), which closely reproduces epidermal differentiation and stratification processes.…”
Section: Introductionmentioning
confidence: 99%